Exploring the concept and consequences of green campaign on social media platforms - Rafidahtul, Abdul Rahim (2022)
The environmental damages have been caused by many factors and most of it is plastic waste. Countless policies have been created to limit the usage of plastic bags globally but still, it is very popular among consumers. Many green campaigns show ineffectiveness when the rate of recycling and plastic use is devastating. The research objective is to understand the concept of the green campaign among consumers and to analyze the consequences of the green campaign in Penang. This research emphasizes the types of social media to create awareness for the green campaign and also reasons to sustain green campaign in Penang Island. This research applied a qualitative research approach and semi-structured interviews with 16 informants in Penang. Each informant chosen using purposive sampling method and need to fill in the criteria such as: lived in Penang for the past 10 years, aware of the No Plastic Bag Campaign and have at least one social media account. This research used the Nvivo method to analyse the qualitative survey to finalize the result. The finding shows that policy plays an important role to ensure society to apply green behaviour such as not using plastic bags; however, lacking facilities is the one that needs to improve as it tends to demotivate them from starting recycling at home. The best social media platform is Facebook, Instagram and Twitter as the communication medium. The informant understand the concept of the green campaign as saving or taking care of the environment but mentioned how they tend to buy the charged plastic bag even with the awareness of what is the consequences of plastic bags to nature. This behavior shows the existence of Cognitive Dissonance theory as the extended theory in Theory of Planned Behavior (TPB) that support the idea of why conflict happens in the behavior intention under the TPB model.